Archaeological mission of Chieti University in Libya. - Menozzi, Oliva, 1968- (RES: reports, excavations and studies of the archaeological unit of the University G. D'Annunzio of Chieti-Pescara ;, 2020)
This volume is dedicated to the archaeological mission in Cyrenaica, starting with the reports and researches of the seasons from 2006 to 2008. The emphasis of the publication is to present archaeological data to form part of an archive of finds, sites and monuments: a resource and reference point for archaeologists from Libya and elsewhere.